Application of the Servqual method to analyze the satisfaction level of hotel services and facilities - Ainun, Nur; Sihombing, Volvo; Masrizal, Masrizal (Sinkron : jurnal dan penelitian teknik informatika, 2021)
With so many hotels and other accommodation facilities in the city of Medan. More and more people are coming and staying and using the facilities at each hotel. Whether it's rooms, meeting room facilities, facilities to hold events, and much more are available in every hotel. Every hotel wants to give satisfaction to guests who come to use the hotel facilities and services. Likewise with SwissbeliNN hotels which have a 3 (three) star classification. Therefore, the opinions of guests and complaints given are very useful to improve the quality of hotel services. To find out, we will look at the satisfaction level of each guest. In this case, the writer applies the servqual method to see the level of guest satisfaction that has been obtained. To find out what is still lacking in the services provided. The purpose of this research is to find out the shortcomings of the hotel for the services provided to hotel visitors, as well as to fulfill the complaints of each visitor to the hotel from the results of the research carried out, with the objectives described later to be able to provide solutions to hotel leaders to fulfill the research results. obtained. The research methods carried out include collecting data directly from the hotel related to the problems that arise to be researched, literature studies, analyzing the problems to be studied based on the data collection that has been obtained, designing applications to overcome problems that arise and making it easier to find out the level of satisfaction of visitors. against managed hotels, as well as testing applications that are made to test the level of success obtained from the application being built. Based on the research conducted, the average perceived service quality score was 3.54. This score is in the somewhat unsatisfactory category when compared with the average score of service quality score which is perceived to be lower than expected. This indicates a gap. The highest average score is given to responsiveness with a value of 3.62 while the lowest score is given to the dimension of empathy with a value of 3.44.